Wolfcry / 4 - Atwater-Rhodes, Amelia (Kiesha'ra, 2006)
Knowing that she must soon choose a mate, twenty-year-old Oliza, heir to the Wyvern throne that unites the avian and serpentine peoples, weighs the political ramifications of her choice while also longing to follow her heart.